The Tyrosine Kinase Activity of c-Src Regulates Actin Dynamics and Organization of Podosomes in Osteoclasts - Destaing, Olivier (The American Society for Cell Biology, 2008)
Podosomes are dynamic actin-rich structures composed of a dense F-actin core surrounded by a cloud of more diffuse F-actin. Src performs one or more unique functions in osteoclasts (OCLs), and podosome belts and bone resorption are impaired in the absence of Src. Using Src(−/−) OCLs, we investigated the specific functions of Src in the organization and dynamics of podosomes. We found that podosome number and the podosome-associated actin cloud were decreased in Src(−/−) OCLs. Videomicroscopy and fluorescence recovery after photobleaching analysis revealed that the life span of Src(−/−) podosomes was increased fourfold and that the rate of actin flux in the core was decreased by 40%. Thus, Src regulates the formation, structure, life span, and rate of actin polymerization in podosomes and in the actin cloud. Rescue of Src(−/−) OCLs with Src mutants showed that both the kinase activity and either the SH2 or the SH3 binding domain are required for Src to restore normal podosome organization and dynamics. Moreover, inhibition of Src family kinase activities in Src(−/−) OCLs by Src inhibitors or by expressing dominant-negative Src(K295M) induced the formation of abnormal podosomes. Thus, Src is an essential regulator of podosome structure, dynamics and organization.